Об экстремумах скорости падения сферического тела переменной массы - Ольшанский, В. П.; Ольшанский, Станислав Васильевич (НТУ "ХПИ", 2007)
The extreme properties of vertical fall speed of a spherical body with linearly changing in time radius are investigated. The conditions of motion speed monotonicity are determined.
Keywords: парашютные системы; газовая среда; скорость витания; тела увеличивающейся массы; тела убывающей массы